Role of Otoendoscopy in Evaluation of Tympanic Membrane Retraction - A New Perspective - Uday Monga; Mahima Luthra; Sampan Singh Bist; Bhartendu Bharti; Vinish Kumar Agarwal (Online Journal of Health & Allied Sciences)
Background: Recently, Otoendoscopy, a novel technique, serves as a pivotal non-invasive diagnostic tool for the initial evaluation of ear disorders. Retraction pockets of the tympanic membrane are clinically significant because they can lead to hearing loss. Therefore, they necessitate careful evaluation and ongoing monitoring. Oto-endoscope because of the wide viewing angle gives a good view of the tympanic membrane status. The objective of this study was to clinically evaluate and grade tympanic membrane retractions and compare otoscopy and otoendoscopy findings. Material and Methods: This was a cross-sectional prospective study. A total 190 ears with tympanic membrane retractions of 111 patients were included in the study. Each of the patients was evaluated for retractions grade according to the Sade and Tos system of classification using pneumatic otoscope and otoendoscope. Results: In 79 (71.2%) patients had bilateral tympanic retraction whereas 32 (28.8%) patients had unilateral. Isolated pars tensa and pars flaccida retraction was found in 109 (57.3%) ears, and 4 (2.1%) ears respectively, while 77 (40.5%) ears having both type of retraction. A cross-tabulation of retraction grades revealed a significant association (p<0.001) between otoscopy and otoendoscopy. A difference in retraction grade findings was seen in 23 (12.1%) ears between otoscopy and otoendoscopy. Conclusion: Otoendoscopy has the potential to become the standard and routine diagnostic, monitoring and teaching procedure for examining tympanic membrane retractions in the outpatient setting. Otoendoscopy having certain definite advantages over otoscopy.